Elimination of the Ultraviolet Spectrophotometric-Based Limitation on the Quantification of Metformin HCl in Acid-Stage Medium for a Comparative Dissolution Testing - Syaiful Choiri; Ilham Kuncahyo; Dwi Larasati (Jurnal Farmasi Indonesia, 2023)
Herein, this work aimed to develop an ultraviolet spectrophotometric assay for metformin HCl in comparative dissolution testing along with the acid stage medium due to low molar absorptivity. Metformin HCl was incorporated into the immediate tablet formulation to mimic the analytical matrix system. The dissolution validation procedure was carried out by linearity, accuracy, precision, the limit of quantification, filter compatibility, and aliquot stability that fulfil the USP method for validation of dissolution procedure, particularly assay of the analyte.The results revealed that metformin HCl had difficulty quantifying in acid pH due to the absence UV-band peak. The addition of pH-shifting agents promoted better performance for metformin quantification. Therefore, the method was successfully developed along with R2, predicted R2, accuracy, and precision of 0.9999, 0,9998, 100.57%, and 1.27%, respectively. In addition, it had the minimum placebo interference (0.47%) and was stable for long-term storage under determined conditions.